Awareness of the concept of hibah as an alternative property management system among students in Diploma Muamalat, in UiTM Puncak Alam / Arif Zafran Khairudin - Khairudin, Arif Zafran (2020)
Hibah is a contract used to show appreciation and love. The purpose of this study is to determine the level of awareness of Students in Diploma Muamalat Part 5, Academy of Contemporary Islamic Studies, UiTM Puncak Alam about the concept of hibah. This study focuses only on the semester 5 students. The total number of students involved is 110 peoples (population). The method used was quantitative through the set of questionnaires using google form help among students of the semester 5. The results showed that the semester 5 students of this program had a mid-level understanding of the concept of the hibah based on the objectives of the study. In conclusion, it still needs a lot of effort to increase level of understanding and knowledge about hibah concept, especially to the whole society.